Disturbed Expression of EphB4, but Not EphrinB2, Inhibited Bone Regeneration in an In Vivo Inflammatory Microenvironment. (18th December 2016) - Shen, Li-Li; Zhang, Li-Xia; Wang, Li-Mei; Zhou, Rong-Jing; Yang, Cheng-Zhe; Zhang, Jin; Yang, Pi-Shan
Abstract : The important role of ephrinB2-EphB4 signaling pathway in bone remodeling has been well established. However, it is still unclear whether this bidirectional signaling also has effects on the regenerative processes of bone defects created in an inflammatory microenvironment. In this study, an experimental animal model of bone defects treated with lentiviruses was prepared and an inflammatory microenvironment was established. Expression levels of bone marker genes were monitored in the newly formed bone tissue using quantitative reverse transcriptase polymerase chain reaction and western blot. Immunohistochemical (IHC) staining and histomorphometric analysis were also performed to evaluate bone healing processes. Compared with the pLenti6.3-ctrl group, the pLenti6.3-ephb4siRNA group exhibited lower expression levels of bone formation marker genes and a higher level of NFATc1 in the new bone tissue. In addition, the newly formed bone was thinner and the number of giant osteoclasts was higher in the pLenti6.3-ephb4siRNA group than that in the pLenti6.3-ctrl group. In contrast, there was no significant difference between the pLenti6.3-efnb2siRNA group and the pLenti6.3-ctrl group. In conclusion, EphB4 plays an irreplaceable role in bone regeneration in an inflammatory microenvironment, whereas the functional loss of ephrinB2 can be effectively compensated, most possibly by other ephrins with similar chemical structures.